Electrolyte for preparing metallographic sample of molybdenum-niobium and molybdenum-titanium alloy and preparation method thereof
Patent Information
- Application Number
- CN202611169230.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]针对现有技术中的不足,本发明提供一种钼铌与钼钛合金金相制样用电解液及其配制方法,解决了传统电解液对两类合金适配性差、易出现过腐蚀、晶界模糊、表面发黑麻点的技术问题
[0009]本发明以高氯酸作为电解质核心,提供电解离子以实现基体的微量均匀腐蚀;无水乙醇作为基础溶剂,兼具调节粘度与抑制氧化的功能;尤为关键的是,乙二醇作为缓蚀稳定组分,通过平衡不同金属相的溶解速率,有效避免了局部过腐蚀;正丁醇则通过改善表面张力,消除微观划痕与麻点,显著提升镜面光洁度。
Smart Images

Figure CN122879803A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallographic sample preparation technology, specifically to an integrated electrolytic polishing and etching electrolyte and its preparation method suitable for metallographic microstructure observation of molybdenum-niobium alloys and molybdenum-titanium alloys. Background Technology
[0002] Molybdenum-niobium alloys and molybdenum-titanium alloys are high-performance refractory alloys with high melting points, high strength, excellent high-temperature oxidation resistance, and thermal shock resistance. They are widely used in high-end fields such as aerospace high-temperature structural components, semiconductor sputtering targets, nuclear energy equipment, and precision instruments. Metallographic analysis is the core testing method for evaluating the grain size, recrystallization degree, second-phase distribution, internal defects, and material properties of these two types of alloys, and high-quality metallographic samples are a prerequisite for accurate testing.
[0003] Currently, the industry primarily uses traditional perchloric acid-ethanol and phosphoric acid-sulfuric acid systems for metallographic sample preparation of molybdenum-based alloys. However, these systems have revealed significant shortcomings in practical applications. First, traditional electrolytes exhibit extremely poor matching rates for the electrolytic dissolution of molybdenum, niobium, and titanium. For molybdenum-niobium and molybdenum-titanium composite alloys, this easily leads to over-corrosion and detachment of the titanium or niobium phases, resulting in blackening of the sample surface, pitting, and blurred grain boundaries, making it impossible to distinguish the second phase from the matrix structure. Second, traditional chemical etching systems often employ strong alkali systems such as potassium ferricyanide or mixed hydrofluoric acid systems. These systems are not only highly toxic and corrosive, posing high operational risks, but also have difficulty in precisely controlling the corrosion rate, resulting in poor repeatability of metallographic sample preparation and large batch-to-batch testing errors.
[0004] In addition, existing commercial electrolytes have limited functionality, only capable of electropolishing or grain boundary etching alone. Polished samples have a smooth surface but lack clear grain boundaries, while etched samples have a rough surface with grinding residue and scratches, requiring different solutions for step-by-step processing. This multi-step operation is not only cumbersome but also prone to introducing impurities during solution changes and cleaning, causing secondary contamination of the samples, damaging the original metallographic structure of the alloy, and significantly affecting the accuracy of the detection. Currently, the industry lacks a dedicated electrolyte that can simultaneously adapt to both molybdenum-niobium and molybdenum-titanium alloys, and can integrate polishing and etching, ensuring safety, stability, and consistent sample preparation results. This makes it difficult to meet the needs of batch, high-precision metallographic detection. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides an electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys and its preparation method, which solves the technical problems of poor compatibility of traditional electrolytes with the two types of alloys, easy over-corrosion, blurred grain boundaries, and blackening and pitting on the surface.
[0006] This invention is achieved through the following technical solution: This invention provides an electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys, comprising the following components by volume percentage: perchloric acid: 5%–12%, anhydrous ethanol: 40%–60%, ethylene glycol: 15%–25%, n-butanol: 8%–15%, and deionized water: balance.
[0007] In a preferred embodiment of the present invention, the volume percentages of each component are preferably as follows: perchloric acid 8%, anhydrous ethanol 50%, ethylene glycol 20%, n-butanol 12%, and deionized water 10%. The electrolyte of this invention is used for the preparation of metallographic samples of molybdenum-niobium alloys with Nb content of 0.5% to 10% and molybdenum-titanium alloys with Ti content of 0.5% to 15%. It can complete the integrated electrolytic polishing and grain boundary etching operation at room temperature without the need for step-by-step solution replacement. Its working parameters are: working voltage 18V to 28V, electrolysis time 6s to 20s, and working temperature 15℃ to 30℃. The optimal working parameters are: working voltage 22V to 25V and electrolysis time 8s to 15s, operating at room temperature.
[0008] This invention also provides a method for preparing the electrolyte for metallographic sample preparation of the above-mentioned molybdenum-niobium and molybdenum-titanium alloys, comprising the following steps: placing the preparation container in an ice-water bath environment, adding a quantitative amount of deionized water, anhydrous ethanol, ethylene glycol, and n-butanol in sequence, and stirring at a uniform speed for 5 minutes to ensure that all components are completely and uniformly mixed; then slowly adding perchloric acid dropwise, stirring continuously throughout the process, and controlling the solution temperature to not exceed 30°C to avoid the solution from becoming ineffective due to high temperature; after the addition is completed, letting it stand for 10 minutes, slightly filtering to remove trace impurities in the solution, and sealing and storing at room temperature for later use.
[0009] This invention uses perchloric acid as the core electrolyte to provide electrolytic ions to achieve micro-uniform corrosion of the substrate; anhydrous ethanol is used as the base solvent, which has the functions of adjusting viscosity and inhibiting oxidation; most importantly, ethylene glycol is used as a corrosion inhibitor and stabilizer to effectively avoid local over-corrosion by balancing the dissolution rate of different metal phases; n-butanol improves surface tension, eliminates micro-scratches and pits, and significantly improves mirror finish.
[0010] The beneficial effects of this invention are as follows: This invention uses a compound system of ethylene glycol and n-butanol to precisely control the difference in electrolytic dissolution rates of the three phases of molybdenum, niobium, and titanium. It can simultaneously adapt to molybdenum-niobium alloys and molybdenum-titanium alloys with different ratios, achieving integrated electrolytic polishing and grain boundary corrosion treatment. This solves the technical problems of poor compatibility of traditional electrolytes with the two types of alloys, easy over-corrosion, blurred grain boundaries, and blackening and pitting on the surface. The prepared metallographic samples have a mirror-like surface without scratches, continuous and clear grain boundaries, uniform microstructure contrast, and no microstructural distortion. At the same time, the electrolyte has good room temperature stability, lower toxicity than traditional electrolytes, is easy to prepare, and has high repeatability. It can meet the needs of metallographic microstructure observation and performance testing of rolled and recrystallized molybdenum-niobium and molybdenum-titanium alloys, and is highly practical and suitable for industry promotion and application. Attached Figure Description
[0011] Figure 1 This is a 100x magnified micrograph of the metallographic structure of the molybdenum-titanium alloy after electrolyte treatment according to the present invention. Figure 2 This is a 100x magnification micrograph of the metallographic structure of the molybdenum-niobium alloy after electrolyte treatment according to the present invention. Figure 3 This is a gold-gold phase micrograph of a molybdenum-titanium alloy after treatment with a traditional perchloric acid-ethanol electrolyte. Detailed Implementation
[0012] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.
[0013] Example 1 In this embodiment, the electrolyte is prepared by volume ratio as follows: 8% perchloric acid, 50% anhydrous ethanol, 20% ethylene glycol, 12% n-butanol, and 10% deionized water.
[0014] Preparation procedure for the drug solution: Place the preparation container in an ice-water bath, and add the deionized water, anhydrous ethanol, ethylene glycol, and n-butanol in the above-mentioned volume ratio in sequence. Stir at a constant speed for 5 minutes to ensure that all components are completely mixed and homogeneous. Then, slowly add perchloric acid dropwise while stirring continuously throughout the process. Strictly control the solution temperature to not exceed 30°C to avoid the drug solution from becoming ineffective due to high temperature. After the addition is complete, let it stand for 10 minutes, then filter slightly to remove trace impurities from the solution. Store in a sealed container at room temperature for later use.
[0015] Sample preparation process: Rolled molybdenum-titanium alloy samples with 8% Ti content were selected and successively water-ground with 150#, 600#, 1000#, 2000#, and 2500# sandpaper. After grinding, the samples were ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried with cold air for later use. 316 stainless steel sheet was used as the electrolytic cathode and the sample to be tested was used as the anode. The electrode spacing was set to 2 cm. Electrolysis was carried out for 12 seconds at room temperature of 22℃ and voltage of 24V. After electrolysis, the sample was taken out, rinsed repeatedly with anhydrous ethanol 3 times, dried with cold air, and then subjected to metallographic microscopy.
[0016] Sample preparation results: such as Figure 1 As shown, the sample surface forms a uniform mirror finish, without any grinding scratches or corrosion pits. The grain boundaries are continuous and straight, without over-corrosion gaps or tissue detachment. The metallographic structure is real and complete, and can be directly used for high-precision metallographic testing and analysis.
[0017] Example 2 In this embodiment, the electrolyte is prepared by volume ratio as follows: 6% perchloric acid, 55% anhydrous ethanol, 18% ethylene glycol, 10% n-butanol, and 11% deionized water.
[0018] The sample prepared for this study was a recrystallized molybdenum-niobium alloy sample with a Nb content of 5%.
[0019] The preparation method of the drug solution is the same as in Example 1. The electrolysis operation parameters are adjusted to: room temperature 20°C, working voltage 22V, electrolysis time 10 seconds. The other sample pretreatment, electrolysis operation, cleaning and drying processes are the same as in Example 1.
[0020] Sample preparation results: such as Figure 2 As shown, the prepared molybdenum-niobium alloy sample has a smooth and flat surface, no corrosion defects, and the distribution of the niobium second phase is clearly distinguishable. The grain boundaries are straight and continuous, and there are no problems such as grain boundary corrosion or tissue detachment. It can accurately complete the measurement of grain size and the analysis of recrystallization degree.
[0021] Example 3 This embodiment is a verification of the upper limit of the formulation range. The electrolyte is prepared by volume as follows: 12% perchloric acid, 55% anhydrous ethanol, 15% ethylene glycol, 8% n-butanol, and 10% deionized water.
[0022] Each core component in this formulation is close to the critical boundary of claim 1: perchloric acid is taken as the upper limit of volume fraction 12%, and ethylene glycol and n-butanol are taken as the lower limit of volume fraction 15% and 8%, respectively, to verify the sample preparation effectiveness and stability of the protection boundary of this electrolyte formulation.
[0023] The preparation process of the drug solution is exactly the same as in Example 1. Due to the increased proportion of perchloric acid, the exothermic effect during the dripping stage is stronger than in Example 1. Therefore, it is necessary to appropriately slow down the dripping rate to ensure that the overall temperature of the solution remains stable at 25-28°C, and to prevent local overheating that could lead to perchloric acid decomposition and drug solution failure.
[0024] Sample preparation process: Rolled molybdenum-titanium alloy samples from the same batch as in Example 1 were selected, and the pretreatment process was the same as in Example 1: the samples were successively water-ground with 150#, 600#, 1000#, 2000# and 2500# sandpaper. After grinding, the samples were ultrasonically cleaned with anhydrous ethanol for 5 minutes and then dried with cold air for later use.
[0025] 316 stainless steel sheet was used as the electrolytic cathode, and the test sample was used as the anode. The electrode spacing was set to 2 cm. Electrolysis was carried out for 15 seconds at room temperature of 23℃ and working voltage of 26V.
[0026] After electrolysis, the sample was removed, rinsed three times with anhydrous ethanol, dried with cold air, and then subjected to metallographic microscopy.
[0027] Sample preparation results: The sample exhibits a uniform mirror-like surface, with all grinding scratches completely removed and no large-area corrosion pitting or blackening. Grain boundaries are consistently discernible, and there is no significant detachment of the matrix structure, meeting the requirements for conventional metallographic observation and grain size rating. Compared to the optimal formulation in Example 1, the sample edge region shows a slight tendency for over-corrosion, a few fine grain boundaries exhibit narrowing notches, and the overall uniformity is slightly reduced. This verifies the effectiveness of the formulation at the upper limit boundary of claim 1 of this invention, while also indicating that this critical ratio is not recommended for high-precision quantitative analysis of the second phase.
[0028] Comparative Example 1 In this embodiment, the core electrolyte perchloric acid is replaced with conventional phosphoric acid, and the electrolyte is prepared by volume ratio as follows: 8% phosphoric acid, 50% anhydrous ethanol, 20% ethylene glycol, 12% n-butanol, and 10% deionized water.
[0029] The preparation process of the drug solution, the sample pretreatment, and the electrolysis operation parameters were completely consistent with those in Example 1, and the same batch of rolled molybdenum-titanium alloy samples were treated.
[0030] Sample preparation results: After electrolysis, the surface of the sample showed no obvious polishing effect, the grinding scratches could not be effectively removed, the grain boundaries could not be seen at all, and the degree of matrix corrosion was extremely weak. It could not achieve the effects of electrolytic polishing and grain boundary corrosion, and it did not have the usability for metallographic sample preparation. This verified the irreplaceable nature of perchloric acid as the core electrolyte.
[0031] Comparative Example 2 This embodiment uses a component ratio that exceeds the range of the formulation of this invention. The electrolyte is prepared by volume as follows: 4% perchloric acid, 60% anhydrous ethanol, 15% ethylene glycol, 7% n-butanol, and 14% deionized water.
[0032] In this formulation, the volume fraction of perchloric acid is 4%, which is lower than the lower limit of 5% in claim 1 of this invention, and the volume fraction of n-butanol is 7%, which is lower than the lower limit of 8%. The overall composition deviates from the formulation range protected by this invention and is used to verify the sample preparation failure outside the lower limit boundary of the formulation.
[0033] The preparation process of the reagent solution, the sample pretreatment method, and the process parameters were completely consistent with those in Example 1, and the same batch of molybdenum-titanium alloy samples were treated. After electrolysis, the samples were cleaned and dried according to the same procedure, and then metallographic observation was performed.
[0034] Sample preparation results: The sample surface could not form a bright mirror finish, and the overall appearance was hazy and dull. Large areas of residual water grinding marks were visible to the naked eye, and there was no obvious electrolytic polishing leveling effect. The surface had no corrosion pits or over-corrosion defects, but the smoothness was far from meeting the requirements for metallographic sample preparation.
[0035] Metallographic microscopic observation showed that the grinding marks remained intact on the surface of the alloy matrix, the grain boundary outlines were blurred and difficult to distinguish, and the contrast of the titanium second phase was weak, making it impossible to carry out grain size statistics, recrystallization degree determination and quantitative characterization of the second phase.
[0036] Causes of failure: The content of perchloric acid as the core electrolyte is too low, resulting in insufficient driving force for dissolution of the electrolytic anode, which cannot eliminate the surface unevenness caused by mechanical polishing; the insufficient content of n-butanol leads to the lack of surface smoothing effect; in addition, the proportion of solvent in the system is too high and the conductivity of the electrolyte decreases, ultimately failing to achieve the integrated polishing-etching sample preparation effect. Comparative Example 3 The traditional molybdenum-based alloy electrolyte formula is adopted: perchloric acid-ethanol system, 10% perchloric acid + 90% anhydrous ethanol.
[0037] Using this conventional electrolyte and with the same process parameters as in Example 1, the same batch of molybdenum-titanium alloy samples were treated. Figure 3 The test results show that the sample surface is blackened over a large area and has a large number of dense corrosion pits, which does not meet the basic requirements for metallographic testing.
[0038] Comparative Example 4 This embodiment adopts the metallographic electrolyte formulation for pure molybdenum materials in the existing published patent (CN 102443841 A). The system is composed of four components: anhydrous ethanol, n-butanol, perchloric acid and deionized water, with a volume ratio of 66:11:33:12. No ethylene glycol corrosion inhibitor was added.
[0039] The preparation process of the drug solution and the sample pretreatment method are consistent with those in Example 1; the electrolysis parameters adopt the optimal process recommended by the patent: room temperature, working voltage 25V, electrolysis time 5s, cathode material and electrode spacing are the same as in Example 1, and the same batch of rolled molybdenum-titanium alloy samples with Ti content of 8% are treated.
[0040] Sample preparation results: The sample surface can only achieve the basic polishing effect of pure molybdenum matrix. The titanium second phase shows obvious preferential dissolution, local detachment and pitting. The grain boundary shows a discontinuous and blurred state, and it is impossible to clearly distinguish the boundary morphology between the matrix structure and the second phase. If the electrolysis time is extended to 8s, the sample edge will show obvious over-corrosion and blackening, which completely fails to meet the requirements of high-precision metallographic detection of molybdenum-titanium alloy.
[0041] The comparison results show that the existing quaternary electrolyte system for pure molybdenum materials, lacking ethylene glycol as a multiphase dissolution rate regulating component, cannot balance the electrolytic dissolution rate difference between the molybdenum matrix and the niobium and titanium alloy phases. It is only suitable for metallographic sample preparation of pure molybdenum and low-impurity molybdenum targets, and is difficult to meet the sample preparation requirements of multi-component molybdenum-based alloys such as molybdenum-niobium and molybdenum-titanium. This verifies the technological advancement of the five-component compound system of the present invention.
[0042] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. An electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys, characterized in that, By volume percentage, it includes the following components: perchloric acid: 5%–12%, anhydrous ethanol: 40%–60%, ethylene glycol: 15%–25%, n-butanol: 8%–15%, deionized water: balance.
2. The electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys according to claim 1, characterized in that, The volume percentages of each component are as follows: perchloric acid 8%, anhydrous ethanol 50%, ethylene glycol 20%, n-butanol 12%, and deionized water 10%.
3. The electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys according to claim 1, characterized in that, The electrolyte is used for the preparation of metallographic samples of molybdenum-niobium alloys with Nb content of 0.5% to 10% and molybdenum-titanium alloys with Ti content of 0.5% to 15%.
4. The electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys according to claim 3, characterized in that, The electrolyte is used for integrated electropolishing and grain boundary corrosion treatment of molybdenum-niobium and molybdenum-titanium alloys.
5. The electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys according to claim 4, characterized in that, The working parameters of the electrolyte are: working voltage 18V~28V, electrolysis time 6s~20s, and working temperature 15℃~30℃.
6. The electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys according to claim 5, characterized in that, The working parameters of the electrolyte are: working voltage 22V~25V, electrolysis time 8s~15s, and operation at room temperature.
7. A method for preparing an electrolyte for metallographic sample preparation of molybdenum-niobium and molybdenum-titanium alloys as described in any one of claims 1-6, characterized in that, The steps include: placing the preparation container in an ice-water bath, adding a measured amount of deionized water, anhydrous ethanol, ethylene glycol, and n-butanol in sequence, and stirring at a constant speed for 5 minutes to ensure that all components are completely mixed; then slowly adding perchloric acid dropwise while continuously stirring throughout the process, controlling the solution temperature to not exceed 30°C to avoid the solution becoming ineffective due to high temperature; after the addition is complete, let it stand for 10 minutes, then lightly filter to remove trace impurities from the solution, and store it in a sealed container at room temperature for later use.
Citation Information
Patent Citations
Metallographic structure electrolytic solution, corrosion method of molybdenum and metallographic structure display method thereof
CN102443841A